EXCITATION study: Unexplained in-custody deaths: Evaluating biomarkers of stress and agitation. (August 2019) - Vilke, Gary M.; Mash, Deborah C.; Pardo, Marta; Bozeman, William; Hall, Christine; Sloane, Christian; Wilson, Michael P.; Coyne, Christopher J.; Xie, Xiaobin; Castillo, Edward M.
Abstract: Background: Law enforcement personnel often confront violent and dangerous individuals suffering from Excited Delirium Syndrome (ExDS) who need emergent medical evaluation and treatment to optimize the best outcomes for this potentially lethal medical emergency. These subjects typically require physical restraint and use of force measures to control them. We sought to determine if stress-related biomarkers can differentiate ExDS subjects when compared with agitation and stress under other circumstances, including agitation and extreme physical exhaustion and restraint coupled with emotional stressors. Methods: This was a prospective multi-center study enrolling a convenience sample of patients who presented with agitation or ExDS. Patients were enrolled from three academic emergency departments (ED), two in the United States and one in Canada. Three study groups (SG) included: SG1) patients brought to the ED with ExDS based on the use of standardized clinical criteria; SG2) ED patients with acute agitation who were not in a clinical state of ExDS but required sedation; SG3) a laboratory control group of subjects exercised to physical exhaustion, restrained, and psychologically stressed with threat of Conducted Energy Device (CED) activation. We examined a panel of stress-related biomarkers, including norepinephrine (NE), cortisol, copeptin, orexin A, and dynorphin (Dyn) from the blood of enrolled subjects. Results: A total of 82 subjects were enrolled: 31 in the agitation group, 21 in the ExDS group, and 30 in the laboratory control group. Data were analyzed, comparing the findings between ExDS and the two other groups to determine if specific stress-related biomarkers are associated with ExDS. Biomarker comparisons between subjects identified with ExDS, agitation, and control groups demonstrated that cortisol levels were more elevated in the ExDS group compared with the other groups. Orexin was only significant in ExDs (with Agitated tendency but lot of variability in the group). NE and Dyn increased as response to stress in Agitated and ExDS. Conclusions: Cortisol levels were more elevated in subjects in the ExDS group compared with the other comparison groups and orexin was elevated in ExDS compared to controls, a trend that did not reach statistical significance in the agitated group. The clinical or diagnostic significance of these difference have yet to be defined and warrants further study. Highlights: Excited delirium syndrome (ExDS) is associated with mortality. There are no pre-mortem tests or markers to assist in defining the diagnosis of ExDS. Levels of cortisone are more markedly elevated in ExDS compared with other agitation. Levels of cortisone are more elevated in ExDS than in strenuous exercise and stress. Levels of orexin trended to being more elevated in ExDS compared to controls.